Jurnal Akuntansi & Investasi: Pengaruh Non Performing Loan Sebagai Dampak Krisis Keuangan Global terhadap Profitabilitas Perusahaan Perbankan - Tia Melya Sari, Dhaniel Syam, Ihyaul Ulum (Akuntansi FE UMY, 2012)
The research purpose is to examine the effect of non-performing loans (NPL) in the global financial crisis on the corporate profitability of banks (listed on the Stock Exchange in 2003-2010). Independent variable in this research is Non Performing Loan (NPL) and the dependent variable is probability by return on asset.Sampling technique is used non-probability purposive sampling, so to be concludedÃ‚ the samples used 15 banks.